АКАДЕМИЧЕСКОЕ ПИСЬМО И ГИПЕРТЕКСТОВЫЕ ТЕХНОЛОГИИ - Абдуллаева, С.Х. (SCIENCE and SOCIETY, 2024)
The article examines hypertext as a media technology that influences the ability to structure one’s own scientific text. The main characteristics of hypertext are presented that provide a didactic model in academic writing.
Keywords: hypertext; academic literacy; information technology; complex competence; hypertext technology